2015
DOI: 10.1111/jeb.12767
|View full text |Cite
|
Sign up to set email alerts
|

Does plasticity enhance or dampen phenotypic parallelism? A test with three lake–stream stickleback pairs

Abstract: Parallel (and convergent) phenotypic variation is most often studied in the wild, where it is difficult to disentangle genetic vs. environmentally induced effects. As a result, the potential contributions of phenotypic plasticity to parallelism (and nonparallelism) are rarely evaluated in a formal sense. Phenotypic parallelism could be enhanced by plasticity that causes stronger parallelism across populations in the wild than would be expected from genetic differences alone. Phenotypic parallelism could be dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
96
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 112 publications
5
96
1
Order By: Relevance
“…In stickleback, transcriptomic plasticity may play a substantial role in migrants’ adaptation to novel environments (Lohman et al., 2017). In this system genetic divergence and plasticity appear to work together in shaping between‐ecotype differences in gene expression (Lohman et al., 2017) and parallel adaptive phenotypic divergence between lake and stream populations (Oke et al., 2016). Our results provide support for the same forces working together in a cichlid lake‐stream system.…”
Section: Discussionmentioning
confidence: 99%
“…In stickleback, transcriptomic plasticity may play a substantial role in migrants’ adaptation to novel environments (Lohman et al., 2017). In this system genetic divergence and plasticity appear to work together in shaping between‐ecotype differences in gene expression (Lohman et al., 2017) and parallel adaptive phenotypic divergence between lake and stream populations (Oke et al., 2016). Our results provide support for the same forces working together in a cichlid lake‐stream system.…”
Section: Discussionmentioning
confidence: 99%
“…This is often seen for primates (Mitteroecker, Gunz, Bernhard, Schaefer, & Bookstein, 2004; Richtsmeier, Corner, Grausz, Cheverud, & Danahey, 1993; Schultz, 1924) and for fish such as Eurasian perch ( Perca fluviatilis ; Svanbäck & Eklöv, 2002). However, species or morphs may show a converging morphology if they experience more similar environments at later life stages, for instance seen for three‐spined sticklebacks and European cave salamanders (Family: Plethodontidae; Adams & Nistri, 2010; Oke et al., 2016). …”
Section: Introductionmentioning
confidence: 99%
“…This result intuitively suggests that some aspect of lake–stream divergence—that what is influenced by these antiparallel genes—must also be antiparallel. Indeed, antiparallel phenotypic divergence for some morphological traits is evident for lake–stream stickleback in the Robert’s versus Misty watersheds (Oke et al , 2016), for lake–stream stickeback in other watersheds (Hendry and Taylor, 2004; Kaeuffer et al , 2012) and for many other fishes (Oke et al , 2017). Recent work has attributed some of this lake–stream phenotypic antiparallelism to antiparallel divergence in lake–stream habitat features (Stuart et al , 2017) and therefore, presumably, antiparallel divergence in lake–stream natural selection.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, these studies have usually examined gene expression in wild-caught individuals (see, for example, Galindo et al , 2010; Manousaki et al , 2013; Westram et al , 2014) that will include an unknown combination of plastic and gene sequence effects on gene expression. Plasticity in such situations can either promote or constrain adaptive divergence (Pfennig et al , 2010; Moczek et al , 2011; Fitzpatrick, 2012; Ghalambor et al , 2015; Oke et al , 2016); but, importantly, plastic expression changes are not encoded by sequence changes, and therefore cannot be used to predict evolutionary trajectories. Yet, other studies have shown that gene expression variation often can be heritable and has contributed to adaptive divergence in several species (Pritchard et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation